Beyond Compliance: Legal Capability as a Dynamic Strategic Resource for Sustainable Competitive Advantage - Anwar Anwar; Romansyah Sahabuddin; Chalid Imran Musa; Deddy Ibrahim Rauf (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
Organizations increasingly operate in environments where regulatory change, technological disruption, and institutional uncertainty directly affect the feasibility and timing of strategic decisions. Yet law is still frequently treated as a compliance boundary rather than as a strategic capability. This article develops Strategic Legal Capability (SLC) as a higher-order organizational capability through which firms sense, interpret, orchestrate, and convert legal and regulatory change into strategic adaptation and sustainable competitive advantage. An integrative literature review combines insights from the resource-based view, dynamic capabilities theory, institutional theory, legal astuteness, legal strategy, and nonmarket strategy. The synthesis identifies four mutually reinforcing dimensions of SLC: legal sensing, legal interpretation, legal orchestration, and regulatory opportunity conversion. The article proposes that SLC improves strategic decision quality and organizational resilience by expanding the firm's feasible strategic options under regulatory uncertainty. It further argues that regulatory complexity, technological disruption, institutional uncertainty, and artificial-intelligence intensity condition the value of SLC. The resulting framework reframes law from an exogenous constraint into an endogenous capability for strategic adaptation. The article contributes a unified construct, a set of testable propositions, and a research agenda for integrating law more deeply into contemporary strategic management.